A Review of the Current State and Recent Changes of the Andean Cryosphere - Masiokas, M. H.; Rabatel, A.; Rivera, A.; Ruiz, L.; Pitte, P.; Ceballos, J. L.; Barcaza, G.; Soruco, A.; Bown, F.; Berthier, E.; Dussaillant, I.; MacDonell, S. (Frontiers in Earth Science, 2020)
The Andes Cordillera contains the most diverse cryosphere on Earth, including extensive areas covered by seasonal snow, numerous tropical and extratropical glaciers, and many mountain permafrost landforms. Here, we review some recent advances in the study of the main components of the cryosphere in the Andes, and discuss the changes observed in the seasonal snow and permanent ice masses of this region over the past decades. The open access and increasing availability of remote sensing products has produced a substantial improvement in our understanding of the current state and recent changes of the Andean cryosphere, allowing an unprecedented detail in their identification and monitoring at local and regional scales. Analyses of snow cover maps has allowed the identification of seasonal patterns and long term trends in snow accumulation for most of the Andes, with some sectors in central Chile and central-western Argentina showing a clear decline in snowfall and snow persistence since 2010. This recent shortage of mountain snow has caused an extended, severe drought that is unprecedented in the hydrological and climatological records from this region. Together with data from global glacier inventories, detailed inventories at local/regional scales are now also freely available, providing important new information for glaciological, hydrological and climatological assessments in different sectors of the Andes. Numerous studies largely based on field measurements and/or remote sensing techniques have documented the recent glacier shrinkage throughout the Andes. This observed ice mass loss has put Andean glaciers among the highest contributors to sea level rise per unit area. Other recent studies have focused on rock glaciers, showing that in extensive semi-arid sectors of the Andes these mountain permafrost features contain large reserves of freshwater and may play a crucial role as future climate becomes warmer and drier in this region. Many relevant issues remain to be investigated, however, including an improved estimation of ice volumes at local scales, and detailed assessments of the hydrological significance of the different components of the cryosphere in Andean river basins.